(untitled) (Acta Entomologica Serbica, 2016)
Moths were collected in Čelarevo (UTM CR81) from 2008 to 2014 by light traps, type RO Agrobecej, with a 250-W mercury lamp; 234,000 specimens were collected of which 223,226 were determined. A total of 292 moth species belonged to the following families: Psychidae 1, Tortricidae 2, Cossidae 4, Limacodidae 1, Crambidae 3, Drepanidae 4, Lasiocampidae 7, Saturniidae 1, Sphingidae 13, Geometridae 55, Notodontidae 14, Erebidae 44 (subfamilies Lymantriinae 7, Arctiinae 15, Herminiinae 2, Hypeninae 2, Rivulinae 1, Scoliopteryginae 1, Calpinae 1, Aventiinae 1, Eublemminae 2, Phytometrinae 1, Erebinae 11), Nolidae 6 and Noctuidae 137. In this paper, data are given for some 194,305 specimens of 155 species (excluding Noctuidae). The finding of Stegania cararia, Cyclophora pendularia, Scopula flaccidaria, Rhyparioides metelkana and Arytrura musculus was significant.